Genealogi al-Dakhil dalam Tafsir al-Qur’an; dari al-Suyuti hingga Ibrahim Khalifah - Basri, Ahmad Faizal; Riyadi, Abdul Kadir (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2022)
Genealogy of al-Dakhil in the Tafsir of al-Qur'an; from al-Suyuti to Ibrahim Khalifah. This study examines al-Asi>l and al-Dakhi>l in the interpretation while the figures studied to explore the study of al-Asi>l and al-Dakhi>l are al-Suyu>ti> and Ibra>hi>m Khali>fah the method used is a literature study with a genealogical analysis. This analysis is used to determine the origin and scientific thread of each generation regarding the study of al-Asi>l and al-Dakhi>l. al-Suyu>ti> or Ibra>hi>m Khali>fah both pay attention to the science of al-Asi>l and al-Dakhi>l Although these two science terms have just been popularized, the practice already exists. It's just that al-Suyu>ti> (d. 1505 AD) with his al-Itqa>n puts forward the science of al-Asi>l, that is the rules that must be learned for commentators and a little explaining al-Dakhi>l . While Ibrahim Khali>fah (d. 2017 M) puts forward the science of al-Dakhi>l, that is things that must be avoided and shunned by commentators, this tendency can be proven by his monumental work al-Dakhi>l fi> al-Tafsi>r.